L’IMEC, centre de ressources en littérature de jeunesse - André Derval; Marie-Pierre Litaudon (Strenae)
Created in 1988 through the initiative of researchers and publishing professionals, the Institut Mémoires de l'édition contemporaine (IMEC) collects, preserves, and promotes archives, as well as studies devoted to major publishing houses, journals, and the various figures regarding a contemporary book’s life and creation: publishers, writers, artists, researchers, critics, graphic designers, booksellers, printers, reviewers, translators, journalists... Since 2004, the IMEC has been located at the Ardenne Abbey, on the outskirts of Caen, where researchers may consult its collections.